Integration of Cognitive Radio with Wireless Sensor Networks for Spectrum Sensing - Kalsi, Puneet; Sharma, Dr. Vikrant (Journal of Advanced Research in Signal Processing and Applications, 2024)
People's daily lives are altering as a result of recent innovations, IoT network growth, and implementation. Due to the growing demands of Internet of Things (IoT) and wireless sensor networks (WSNs), The utilization of wireless systems has surged recently and is expected to grew significantly in the near future. In wireless cognitive sensor networks, spectrum sharing allows networks to function together by sharing some of the available spectrum, particularly when there is an extra band that is not being used. Additionally, a creative framework for the smooth integration of Visible Light Communication (VLC) and Cognitive Radio Sensor Network (CRSN) technologies is presented, offering a novel solution to difficulties related to spectrum      shortages      and      increasing      network      efficiency.      The      difficulties of the upcoming generation of Internet of Things networks are still to increase throughput whil e maintaining reliability and decrease total network latency. This paper makes a contribution to wireless sensor networks and cognitive radio combined technologies to provide spectrum availability, data bandwidth and benefits of using CR with Wireless Sensor networks.